Microhabitat use by scorpions in a tropical dry forest relict of the Colombian Caribbean - Álvarez, Deivys; Gómez, Diego; Martínez, Jairo; Mendoza, Hansell; Ruiz, Santiago (Revista Colombiana de Entomología, 2013)
Microhabitat use by scorpions was studied in the Reserva Forestal Protectora Serranía de Coraza, department of Sucre, a tropical dry forest relict of the Colombian Caribbean. The scorpions were collected between 19:00 and 00:00 hours by searching using an ultraviolet lamp and entomological forceps, and were preserved in 70% ethanol. One hundred nine individuals belonging to four species were captured. Opisthacanthus elatus was the most frequent (n = 53), followed by Tityus tayrona (n = 28), Tityus asthenes (n = 26) and Ananteris columbiana (n = 2). Opisthacanthus elatus and Tityus asthenes were found significantly associated with low or within objects on the ground microhabitat and had a niche overlap of 91%. Tityus tayrona was collected only in low vegetation and A. columbiana was captured on fallen leaves and low vegetation. This is the first report on scorpion microhabitat use in Colombia.